Analisis Kualitas Pelayanan Berbasis Preferensi Konsumen: Studi Kasus Pada Bengkel Kendaraan Roda Empat - Humiras Hardi Purba; Fransisca Debora; Tosty Maylangi Sitorus; Siti Aisyah; Choesnul Jaqin (Politeknik ATI Padang, 2022)
Product and service quality factors are important aspects of business continuity. Consumers will abandon low-quality products and services. Consumers will feel satisfied if all aspects of the products and services are appropriately accommodated. Product and service quality have different tendencies because service quality dimensions are more complex than product quality. This study aims to analyze the quality of customer service at auto repair shops based on consumer preferences. Assessment of the level of satisfaction and consumer expectations of each attribute is done by filling out a questionnaire to identify the gap between the level of importance and level of performance. The consumer's assessment of each indicator of the auto repair shop is carried out through a questionnaire filled out to the consumer to find out the gap between the level of importance and the level of performance. The analytical method used is Importance Performance Analysis–IPA showing that the attributes of auto repair shops that need to be improved are [P1] improving the repair period as promised, [P2] Procedures and managerial capabilities in providing adequate service, [P3] Results following consumer recommendations, and [P4] Knowledgeable workshop managers and staff, [P5] Service speed from responsiveness quality dimensions, [P11] Credibility and honesty of workshop managers and staff, [P12] Clarity of communication and information to consumers. The priority of quality attributes of auto repair shops that will be improved can provide alternative development priorities between human resources and limited equipment servicing.